Further development of the reflective practice questionnaire - Shane L. Rogers; Lon Van Winkle; Nicole Michels; Cherie Lucas; Hassan Ziada; Eduardo Jorge Da Silva; Amit Jotangia; Sebastian Gabrielsson; Silje Gustafsson; Lynn Priddis (PeerJ, 2024)
Background This article provides an update of the Reflective Practice Questionnaire (RPQ). The original RPQ consisted of 40-items with 10-sub-scales. In this article, the RPQ is streamlined into a 10-item single reflective practice construct, and a 30-item extended version that includes additional sub-scales of confidence, uncertainty/stress, and work satisfaction. Methods A total of 501 university students filled out an online questionnaire that contained the original Reflective Practice Questionnaire, and two general measures of reflection: The Self-Reflection and Insight Scale, and the Rumination-Reflection Questionnaire. Results Based on factor analysis, the RPQ was streamlined into a brief 10-item version, and an extended 30-item version. Small positive correlations were found between the RPQ reflective practice measure and the two measures of general reflection, providing discriminant validity evidence for the RPQ. The RPQ was found to be sensitive to differences among industries, whereas the general measures of reflection were not. Average reflective practice scores were higher for health and education industries compared to retail and food/accommodation industries.